PENGARUH SALES PROMOTION DAN INFLUENCER MARKETING TERHADAP MINAT MEMBELI DALAM MOBILE LEGENDS - Carissa, Tiffani; Aruman, Akhmad Edhy (Universitas Serang Raya, 2019)
This research examines sales promotion, influencer marketing and purchase intention ofMobile Legends Bang Bang game. This research aims to determine whether there is influence and theextent of the influence of sales promotion and influencer marketing towards the in game purchaseintention. The communication model used is technology acceptance model by Venkatesh and Davis.The methodology in this research is a quantitative approach using multiple linear regression analysis.The population of this research is Mobile Legends game players who have seen the sales promotion inthe game and influencer marketing through BluePanda?s YouTube channel. Primary data werecollected by distributing questionnaires to 100 respondents. From the research?s result, there is aninfluence on sales promotion and influencer marketing simultaneously towards in game purchaseintention with values of contribution equal to 32.3%.